Pelatihan Penggunaan Teknologi, Inovasi Dan Evaluasi Pengembangan Kualitas Pendidikan - Mesterjon, Mesterjon; Siska, Jumiati; Sukirdi, Sukirdi; Herlina, Yuni; Saipul, Saipul; Cianstury, Irvan; Hamzani, Hamzani (Universitas Dehasen Bengkulu, 2025)
In the era of globalisation, technology has become an important element in various sectors, including education. SMPN 21 Bengkulu City recognises the need to improve the quality of education through the application of technology, innovation and systematic evaluation. For this reason, a training themed ‘Use of Technology, Innovation, and Evaluation to Develop the Quality of Education’ was held to improve the competence of teachers and education personnel in utilising technology optimally. The training was designed to address the challenges of 21st century education, where educators are not only required to master traditional learning methods but also be able to utilise technology to create interactive and relevant learning. Educational innovation through the use of digital platforms, technology-based learning media, and learning evaluation applications are the main focus of this activity. This activity lasted for three days, involving educational technology experts, lecturers, and competent practitioners. The materials presented included the utilisation of Learning Management System (LMS), technology integration strategies into learning, and data-based evaluation techniques to assess learning success. The results of this training showed a significant increase in participants' ability to design, implement, and evaluate technology-based learning. In addition, participants are encouraged to continue to innovate in creating learning methods that are adaptive to student needs. Through this training, SMPN 21 Bengkulu City is committed to being a pioneer in improving the quality of technology-based education, in line with the school's vision to produce a generation that is ready to face the challenges of the digital era. This training is expected to be the first step in creating a progressive, innovative and future-oriented education ecosystem.